PEMBERIAN REMISI KEPADA WARGA BINAAN DI LEMBAGA PEMASYARAKATAN LAKI-LAKI DEWASA KELAS 2 A KUPANG - Indriani Jesica Jawa, Mariani; Charmelo Ngganggu, Fredenrik; Mone, Alecadros; Hendrikson Tangpada, Daniel; Yanri Ariyanto Fallo, Umbu; Sugiyani Boleng, Yosephin (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This article discusses the provision of remission to inmates at the Kupang Class 2 A Adult Male Correctional Institution, which is part of social rehabilitation and inmate development efforts. Remission is given as a form of appreciation for inmates who show good behavior while serving their sentences. This study aims to identify the procedure for granting remission, the criteria used, and the impact of granting remission on the behavior and rehabilitation of inmates. The results of the study show that the provision of remission is not only a reduction in the sentence period, but also as a motivation for the inmates to improve themselves and behave positively. The provision of remission has a long-term goal to support the social reintegration of prisoners after they complete their sentences, as well as to strengthen a more humane and rehabilitative correctional system